Study of the press forming mechanism of a thermoforming machine. (July 2014) - Belforte, Guido; Colombo, Federico; Raparelli, Terenziano; Maffiodo, Daniela
The paper presents kinematic and dynamic investigations of the main press forming mechanism of a thermoforming machine. A multibody analysis of this press forming mechanism, which lifts and rotates a press bed, was carried out. Press bed lifting, which is necessary to form the component, is performed by means of a first rod and toggle mechanism. Press bed rotation to eject the formed component is produced by means of a second rod and must be appropriately shifted. These rods are oscillating followers driven by cams, making it possible to precisely define trajectories as a function of the motor shaft rotation angle. Analysis is performed by numerically solving the equations of motion. Cam synthesis on the basis of the oscillating followers' trajectories makes it possible to obtain cam profiles in order to evaluate pressure angles and check that there is no undercutting. System dynamics is investigated in order to evaluate motor torque and analyse internal stresses on the hinges. In addition, some experimental results and those obtained with the dynamic model are compared. Performance improvement of the actual machine is carried out by modifying the trajectory of the press bed by means of a numerical code at the purpose developed. This approach is more convenient than the use of a commercial multibody code, which is not specifically built for parametric studies.